Case Based Reasoning Method for Diagnosing Air Conditioner Damage - Angga Redy Saputra (Universitas Putra Indonesia YPTK Padang, 2022)
Technological advances greatly impact the continuity and comfort of human life, for example the use of air conditioners (AC). AC is a room conditioning tool that is able to condition the air in the room and provide a comfortable effect on the body. Air conditioning (AC) is a system or machine designed to stabilize air temperature and humidity in a certain area by circulating refrigerant gas through the refrigeration process. The research framework created in this research methodology aims to get the results as expected and easy to solve problems and easy to understand. In collecting data, researchers obtain data from various sources such as journals, books and other references to the object of research. This research was carried out by applying the interview method directly to Cv. Ihfha belongs to Mr. Jean Hilman. With an Expert System using the Case Based Reasoning (CBR) method, it can help employees work more elegantly and efficiently because all data collection about damage to the air conditioner is already in the system, so the owner can find out what is the damage to the air conditioner and can be done faster. the owner can already find out what damage is to the AC and can be done more quickly